Innovations in Computational Intelligence Best Selected Papers of the Third International Conference on REDSET 2016 (Studies in Computational Intelligence,, 2018)
The present book includes a set of selected best papers from the 3rd International Conference on Recent Developments in Science, Engineering and Technology (REDSET 2016), held in Gurgaon, India, from 21 to 22 October 2016. The conference focused on the experimental, theoretical and application aspects of innovations in computational intelligence and provided a platform for the academicians and scientists. This book provides an insight into ongoing research and future directions in this novel, continuously evolving field. Many decades have been devoted to creating and refining methods and tools for computational intelligence such as Artificial Neural Networks, Evolutionary Computation, Fuzzy Logic, Computational Swarm Intelligence and Artificial Immune Systems. However, their applications have not yet been broadly disseminated. Computational intelligence can be used to provide solutions to many real-life problems, which could be translated into binary languages, allowing computers to process them. These problems, which involve various fields such as robotics, bioinformatics, computational biology, gene expression, cancer classification, protein function prediction, etc., could potentially be solved using computational intelligence techniques.